Zoning practices: enhancing tourists' experience in coastal resorts - Mat Raschid, Mohammed Yazah; Sharif, Roslina; Utaberta, Nangkula (Jabatan Seni Bina, Fakulti Kejuruteraan & Alam Bina, Universiti Kebangsaan Malaysia, 2014)
The zoning in most of the resorts is not only used as a planning tool to enhance the environmental and social experience but also to allow tourist to feel safe in the resort. The purpose of this paper is to identify the spatial characteristics of zoning that assist in promoting environmental and social experience in spaces created by the siting process in the three main resorts which are Malaysia’s premier resorts. A physical observation of general pattern of zoning in the three main case study resorts; Berjaya Langkawi Beach & Spa Resort, Langkawi Island, (Northern Region), PangkorLaut Resort, Pangkor Island, Perak (Central Region) and The Avillion Village Resort, Port Dickson, Negeri Sembilan (Southern Region) in correlation with fifteen other resorts in the three case study sites was conducted. Findings show the general patterns of physical data characteristics of the case study resorts indicates the variations across the resorts in terms of the provision of circulation spaces and the arrangement and provision of type of units, open spaces and amenities. This paper exposes few important gaps in conservation of natural environment, accommodating resorts coastal and building setbacks, maximizing view, as quality transitional spaces, transportation and building forms and shapes. The spatial qualities through proper zoning are crucial to control the tourists’ movement and activities whilst ensuring they can interact with the particular environment and the local community. The paper concludes that while the basic characteristics such as sizes and building heights is formally regulated by the authority through specific guidelines, they are insufficient to facilitate the experience without taking into consideration of the tourists and local views.